A framework to evaluate land degradation and restoration responses for improved planning and decision-making. Issue 1 (1st January 2020) - Pandit, Ram; Parrotta, John A.; Chaudhary, Ashok Kumar; Karlen, Douglas L.; Vieira, Daniel Luis Mascia; Anker, Yaakov; Chen, Ruishan; Morris, Joe; Harris, Jim; Ntshotsho, Phumza
ABSTRACT: Avoiding, reducing or reversing land degradation will require increased restoration investments, carefully targeted and implemented to maximize environmental, economic and social benefits. Our objective was to develop a multi-criteria framework to assess effectiveness of land degradation responses for enhanced land use planning and restoration by evaluating both direct biophysical and socio-economic responses and indirect effects of various restoration strategies. The effectiveness of restoration responses is demonstrated for degraded forestland using a comprehensive literature review and case study in Nepal. The results show that most forestland restoration responses have an ecological focus with tree planting being the dominant direct response and economic and financial instruments the indirect responses. The results confirmed that environmental desirability was the dominant factor and economic feasibility was secondary for assessing restoration responses. Cultural acceptability was given the least consideration. Among sub-criteria, improved vegetative structure was the dominant restoration response. This study, originating from the Land Degradation and Restoration Assessment of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, supports the view that the scientific community and decision-makers must give greater attention to cultural, social, technical, and political dimensions that influence the outcomes of restoration responses to solve the pervasive problem of land degradation.